Material Aspects of Reading in Ancient and Medieval Cultures. Materiality, Presence and Performance - Schücking-Jungblut, Friederike (Materiale Textkulturen, 2020)
This publication seeks to endeavour the relationship between material artefacts and reading practices in ancient and medieval cultures.While the acts of reception of written artefacts in former times are irretrievably lost, some of the involved artefacts are preserved and might comprise hints to the ancient reading practices. In form of case studies, the contributions to this volume examine various forms of written artefacts as to their implications on modes of reading. Analyzing different Qumran scrolls, codices, Tefillin, Mezuzot, magical texts, tablets, bricks, and statues as well as meta-textual and iconographic aspects, the articles inquire the possibilities of how to correlate material aspects to assumed modes of reception and practices of reading. The contributions stem from Egyptology, Papyrology, Qumran Studies, Biblical Studies, Jewish Studies, Ancient Christianity, and Islamic Studies.In total, this volume contributes to the research on practices of reception in times past and demonstrates the potential hidden in text-bearing artefacts.